2021
DOI: 10.1111/1365-2745.13676
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of a biocontrol agent on a native plant causes an indirect trait‐mediated non‐target effect on a native insect

Abstract: Identifying food web linkages between biocontrol agents of invasive plants and native species is crucial for predicting indirect non‐target effects. Biocontrol insects can integrate into food webs within recipient habitats and influence native insects through apparent competition (altering shared natural enemies) or density‐mediated exploitation competition (changing density of native plants). However, whether and how trait‐mediated exploitation competition (modifying native plant chemicals and volatiles profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…FM, fresh mass feeding intensity increased. These findings coupled with the fact that flea beetle larval survival was positively correlated with each carbohydrate and negatively correlated with tannin across all feeding treatments suggested that changes in plant quality might underlie observed plant-mediated density-dependent interactions between herbivores (He et al, 2021;Robert et al, 2012b;Soler et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…FM, fresh mass feeding intensity increased. These findings coupled with the fact that flea beetle larval survival was positively correlated with each carbohydrate and negatively correlated with tannin across all feeding treatments suggested that changes in plant quality might underlie observed plant-mediated density-dependent interactions between herbivores (He et al, 2021;Robert et al, 2012b;Soler et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, with adult flea beetle feeding, increased the three carbohydrates and reduced tannin only occurred as feeding intensity was initially increasing, before it attenuated and finally reversed as feeding intensity increased. These findings coupled with the fact that flea beetle larval survival was positively correlated with each carbohydrate and negatively correlated with tannin across all feeding treatments suggested that changes in plant quality might underlie observed plant‐mediated density‐dependent interactions between herbivores (He et al, 2021; Robert et al, 2012b; Soler et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…US herbivore-free plants. It has been shown that China populations of T. sebifera differ in the amounts and types of VOCS produced depending on the identity of the herbivore that attacks them (Sun et al 2019, 2022, He et al 2021) as is the case for most plants (Takabayashi 2022). Differences in the VOCs of native vs. invasive plants have also been shown, with some showing greater VOCs for invasive populations or different relative concentrations of compounds, depending on population origin (Zangerl et al 2008, Wolf et al 2011, Franks et al 2012, Lin et al 2021).…”
Section: Discussionmentioning
confidence: 99%